Distribution of rotavirus genotypes associated with acute diarrhoea in Zimbabwean children less than five years old before and after rotavirus vaccine introduction. Issue 47 (12th November 2018) - Mukaratirwa, Arnold; Berejena, Chipo; Nziramasanga, Pasipanodya; Ticklay, Ismail; Gonah, Archebald; Nathoo, Kusum; Manangazira, Portia; Mangwanya, Douglas; Marembo, Joan; Mwenda, Jason M.; Weldegebriel, Goitom; Seheri, Mapaseka; et al.
Abstract: Background: Sentinel surveillance for diarrhoea is important to monitor changes in rotavirus epidemiological trends and circulating genotypes among children under 5 years before and after vaccine introduction. The Zimbabwe Ministry of Health and Child Care introduced rotavirus vaccine in national immunization program in May 2014. Methods: Active hospital-based surveillance for diarrhoea was conducted at 3 sentinel sites from 2008 to 2016. Children aged less than 5 years, who presented with acute gastroenteritis as a primary illness and who were admitted to a hospital ward or treated at the emergency unit, were enrolled and had a stool specimen collected and tested for rotavirus by enzyme immunoassay (EIA). Genotyping of positive stools was performed using reverse-transcription polymerase chain reaction and genotyping assays. Pre-vaccine introduction, 10% of all positive stool specimens were genotyped and all adequate positive stools were genotyped post-vaccine introduction. Results: During the pre-vaccine period, a total of 6491 acute gastroenteritis stools were collected, of which 3016 (46%) tested positive for rotavirus and 312 (10%) of the rotavirus positive stools were genotyped. During the post-vaccine period, a total of 3750 acute gastroenteritis stools were collected, of which 937 (25%) tested positive for rotavirus and 784 (84%) were genotyped. During the pre-vaccine introduction the most frequent genotype was G9P[8] (21%) followed by G2P[4] (12%), G1P[8] (6%), G2P[6] (5%), G12P[6] (4%), G9P[6] (3%) and G8P[4] (3%). G1P[8] (30%) was most dominant two years after vaccine introduction followed by G9P[6] (20%), G2P[4] (15%), G9P[8] (11%) and G1P[6] (4%). Conclusion: The decline in positivity rate is an indication of early vaccine impact. Diversity of circulating strains underscores the importance of continued monitoring and strain surveillance after vaccine introduction.